Curriculum Design for Teaching Arabic as a Foreign Language: A Competency-Based Education Model / تصميم المنهج لتعليم اللغة العربية للناطقين بغيرها: نموذج التعليم القائم على الكفايات - Hassanain el-Birun; Richard David (IJAS: International Journal of Arabic Studies, 2026)
The teaching of Arabic as a foreign language requires curriculum designs that are capable of responding to the linguistic needs of learners while aligning with contemporary educational frameworks. This study aims to examine the implementation of a competency-based education model in the curriculum design for teaching Arabic as a foreign language. The research adopts a qualitative descriptive approach by analyzing curriculum documents, instructional strategies, and learning outcomes applied in Arabic language programs. Data were collected through document analysis, classroom observations, and interviews with Arabic language instructors. The findings indicate that a competency-based curriculum facilitates the systematic development of learners’ linguistic competencies, including listening, speaking, reading, and writing skills. In addition, the integration of communicative tasks and contextual learning activities enhances learners’ engagement and supports the practical use of Arabic in real communicative situations. The study also reveals that clearly defined competency standards help instructors design structured learning activities and assessment strategies that align with expected learning outcomes. Therefore, the competency-based education model can serve as an effective framework for improving the quality of Arabic language instruction in foreign language contexts.